Design, Validity and Effect of an Intra-Curricular Program for Facilitating Self-Regulation of Learning Competences in University Students with the Support of the 4Planning App - Karla Lobos; Fabiola Sáez-Delgado; Daniela Bruna; Rubia Cobo-Rendon; Alejandro Díaz-Mujica (MDPI AG, 2021)
Background: Smartphone applications have the potential to support university students for the benefit of learning in higher education. Objective: To design and evaluate the effect of an intra-curricular program using a mobile application on self-regulated learning strategies in university students. Method: The 4Planning mobile application was designed following a systematic literature review, expert judgement and application. The instrument to assess the effect of the intervention was the SRL Readiness Practices Scale, with a one-factor structure (CFI = 0.98; TLI = 0.97; RMSEA = 0.05) with reliability of α = 0.89. The design was quasi-experimental with pre- and post-test measures and experimental and control groups. The sample consisted of 473 first-year university students (37.02% male) from seven Chilean universities with a mean age of 19.35 (SD = 2.49). Statistical analysis was an ANOVA performed in R software version 4.0.3. Results: Statistically significant differences were identified in the levels of self-regulated learning between the experimental group compared to the control group. Conclusion: The development of the 4Planning app proved to be effective in promoting the development of self-regulated learning strategies in university students.